Regsubjektiwiteit ’n prinsipiële benadering - Pienaar, G. J. (Koers, 1983)
Legal subjectivity is the capacity of an entity to act as a subject in the processes of law. In my opinion only man can act as a legal subject. Seen from a Christian point o f view, God created man to H is image, and placed him on earth as the pinnacle, o f creation, to subject, cultivate and protect that creation. To confer legal subjectivity upon something else that man would detract from man's Godgiven status.